Exploring the Relationship between Urban Form, Mobility and Social Well-Being: Towards an Interdisciplinary Field of Sustainable Urban Planning and Transport Development - Cao, Mengqiu; Papaix, Claire; Yang, Tianren; Büttner, Benjamin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on exploring the relationship between urban form, mobility, and social well-being across neighborhoods, cities, and regions. Understanding more about these relationships is helpful in shaping integrated sustainable urban planning and transport development strategies. All reprint chapters primarily contribute to the existing literature on the interdisciplinary field of the impact of urban planning and transport on social well-being and facilitate novel ways of measuring the abstract concept of well-being, particularly in Asian and European countries. We suggested that further research could explore these themes in greater depth by means of both theoretical frameworks and methodological developments in this integrated field.